Development of a functional rice bran cookie rich in γ-oryzanol - de Souza, Carla Beatriz [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Borges, Cristine Vanz [UNESP]; Dias, Luiza Cristina Godim Domingues [UNESP]; Spoto, Marta Helena Fillet; Castro, Gustavo Rocha [UNESP]; Corrêa, Camila Renata [UNESP]; Minatel, Igor Otavio [UNESP] (Springer Nature, 2019)
Rice bran (RB) is a rice milling by-product and an interesting source of fibers and bioactive compounds as γ-oryzanol. These food compounds are capable of prevent and/or improve metabolic disorders associated to chronic diseases. To provide a good source of bioactive compounds and a better destination for RB, the aim of this study was to develop and evaluate the antioxidant potential of functional cookies made with this by-product. Five different formulations containing 25, 50, 75 and 100% of RB were studied and, in the control formulation, RB was substituted by polished rice flour. Cookies were analyzed up to 30 days of storage, regarding the levels of fibers, γ-oryzanol and lutein. The antioxidant capacity was determined through DPPH ● and FRAP assays. The shelf life was determined through microbiological analyses and the acceptance was evaluated by means of hedonic scale acceptance test and purchase intention test. There was a significant difference (p < 0.05) among the formulations regarding the fibers content, γ-oryzanol, lutein and antioxidant capacity, which values increased according to the RB content in the composition. Sensory analysis showed a higher acceptance of the formulations with RB the control cookies, with preference for the cookie containing 75% of RB. Cookies containing RB can be produced at low cost, becoming accessible to consumers, and provide an effective alternative to improve the population nutrition and the utilization of this by-product.
Keywords: Antioxidants; By-products; Dietary fiber; Phenolic compounds; Sensory analysis; Shelf life